ANALISIS PENGGUNAAN YIELD SPREAD OBLIGASI UNTUK MENENTUKAN TIMING INVESTASI DI PASAR SAHAM INDONESIA DENGAN MENGGUNAKAN MODEL PROBIT - , Dody Tambunan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of the paper is to time the stock market by using probit modelling. We will accomplish this task by testing the significance of different financial variables. The yield spread, which has already been proved to be effective for several established markets, will play a central role in our analysis. Primarily we will extend the analysis of Liu, Resnick and Shoesmith (2004) to verify whether the slope of the Indonesian and U.S. yield curve can offer important information also to time the Indonesia stock market, thus providing the opportunity to construct a better portfolio as compared to the benchmark of the buy-and-hold strategy on the stock market. We also will measure which combination of the yield spread of multiple Indonesian and US fixed income securities that is the best to predict the Indonesian stock market. For the short term fixed income securities we used 3- month period as benchmark and for long term fixed income securities we use 5-year, 7- year, 8-year and 10-year period. In the so many models with with different complexity level that already developed in aim to time the market effectively, we want to show how a relatively simple model can offer a fairly reliable solution to the choice of timing the investments on the stock market.